2 International guideline for the management of acute low back pain in rowers – a proposal for an athlete care pathway. (20th December 2017) - Thornton, JS; Vinther, A; Wilson, F
Abstract : It is estimated that up to 84 percent of adults have low back pain (LBP) at some time in their lives, with the 12 month incidence reported as 3%–18% worldwide. In the sport of rowing, between 32%–53% of athletes will experience LBP within a given year while point prevalence in adolescent rowers may be as high as 65% and 53% in males and females respectively. The lumbar spine is the most frequently injured region, accounting for up to 53% of all reported injuries amongst rowers with an incidence between 1.5 and 3.7/1000 hour of rowing and associated training. For many individuals, episodes of back pain are self-limited. The effect on rowers' sporting careers, life-long disability and chronic pain, however, is unknown. Anecdotally, it is the injury most likely to be career-ending for rowers. There is no common strategy to address LBP in rowers despite evidence that specific information on management is desired by the rowing population worldwide. Thus, it is proposed that a consensus statement outlining best practice in the management of rowing LBP is produced and disseminated within the international rowing and sports medicine communities. An evidence-based approach using recent advances in understanding of factors associated with injury onset (including exposure, biomechanics and other intrinsic and extrinsic risk factors) is leading to the creation of the new guideline using both expert knowledge and the current evidence. A detailed literature search was conducted, reviewing the incidence/prevalence, risk factors, diagnosis and management of LBP in rowers. Discussions are being held between the authors and key experts (clinicians and researchers) in the international community to assimilate information and highlight key issues. To date, key research findings for optimal prevention and management include: type and mode of ergometer use, optimal lumbopelvic rhythm (moving through hips) and optimal loading including adequate recovery. The creation of this new guideline for management of LBP in rowers is designed to aid readers through diagnosis, investigations and management of LBP with a longer version for clinicians; it aims to be both user friendly and informative. This presentation will outline the steps taken and findings of this novel approach to reach consensus on an Athlete Care Pathway for LBP in rowers.